Opportunities and Challenges of Utilising Big Data on SATUSEHAT Platform in Nursing: A Literature Review - Yesica Tria Enggriani; Rr Tutik Sri Haryati (Lentera Perawat, 2024)
The SATUSEHAT platform which is Indonesia Health Services (IHS) is a form of digital transformation initiated by the Indonesian Ministry of Health. This platform integrates the health data of all Indonesian people including medical records across health facilities which will develop into a national health data center and has the opportunity to become big health data for the Government. To face this, the nursing field must prepare for various opportunities and challenges. Objective: To provide an overview of the opportunities and challenges of utilizing big data through the SATUSEHAT platform in the nursing field. The method used in this research is literature review. The keywords used were Big data in nursing and The Application of big data for the future. Literature searches were conducted using the online database method starting from 2015-2022 through ScienceDirect, ProQuest and Clinical Key.  As a result of the literature review with a case study design, it was found that opportunities for big data utilization include personalized care, nursing research development, data-based policy formulation, while challenges include increasing data processing and management competencies, integrating big data education curriculum, privacy and ethical issues and standardizing nursing terminology Recommendations It is hoped that further research can discuss the preparations that must be made to maximize the potential for big data utilization in the future.